Analisis Daya Saing Tapioka (Kode HS 1903) di Pasar Internasional - Rozak, Dede Abdul; Rozak, Elmira Syahdanabila (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Competition in the international market for tapioca commodities  is getting tougher with the presence of other major exporting countries. Therefore, it is important for Indonesia to not only rely on comparative advantages but also strengthen its competitive advantages. The purpose of this study is to analyze the competitiveness of tapioca in Indonesia and four competing countries. The data analysis used in this study are ISP, AR, RCA, RSCA, TBI, and ECI. The results showed that Indonesia's tapioca trade balance had a positive performance in the period 2013-2022. The competitiveness of tapioca exports based on the Index of Trade Specialization (ISP) shows that Indonesia has strong competitiveness with an average ISP value of 0.59. The competitiveness of tapioca exports based on the average value of Indonesia’s Acceleration Ratio (AR) is 9.38 which means that tapioca have a comparative advantage. The competitiveness of tapioca exports based on the average value of Indonesia's Revealed Comparative Advantage (RCA) is 3.71, which shows that tapioca have a comparative advantage. Likewise, the results of the RSCA analysis show the same thing. The competitiveness of tapioca exports based on the average value of Indonesia's Trade Balance Index (TBI) is 0.59, which means that it can run as an exporting country, because it is able to export more than importing tapioca. The competitiveness of tapioca exports based on the average value of Indonesia's Export Competitiveness Index (ECI) 1.05, which shows a competitive advantage or is experiencing an upward trend in tapioca exports.